Acute Abdomen in Children - Keler de Oliveira, Claudia; Santoro Angelo Zaragoza, Simone; de Oliveira Junior, Wilson Elias; Marques, Rozemeire Garcia [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Takegawa, Bonifácio Katsunori [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Bischoff, Andrea (Springer Nature, 2025)
In the emergency department, firstly, whenever a physician comes across a pediatric patient with acute abdominal pain, it is important to evaluate signs and symptoms through history and physical exams. Investigation of the abdominal pain symptoms is important to discriminate whether the patient will require surgical intervention. One possible diagnostic approach involves categorizing the abdominal pain as a syndrome—acute abdomen, as well as performing a systematic approach regarding its etiology, for example, the following: (a) obstruction, (b) inflammation, or (c) trauma. In this scenario, a diagnosis must consider, for instance, the presence of worrisome features, associated systemic signs and symptoms, past medical history, and the age of the patient. This can be done from clinical presentation: